Increasing Repurchase Intention Through Timeliness Delivery and Service Quality Mediated by E-Commerce Customer Satisfaction in Indonesia - Edhie Budi Setiawan; Harry Purwoko; Hilya Fisar Nazwany; Asnia Harun (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
In the marketplace category e-commerce sites that have the highest number of visitors in Indonesia are Shopee, Tokopedia, Lazada, Blibli, and Bukalapak. The number of Blibli visitors looks lower compared to other E-Commerce, but still increases in 2023. The purpose of this study is to increase repurchase intention through timeliness delivery and service quality mediated by e-commerce customer satisfaction in Indonesia. This study involved 170 respondents who were Blibli e-commerce users, with samples taken using purposive sampling techniques. The method applied in this study is quantitative, with data processing using SEM-PLS software. The results of this study indicate that Timeliness delivery has a significant effect on customer satisfaction. Timeliness delivery does not have a significant effect on repurchase intention. Service quality has a significant effect on customer satisfaction and repurchase intention. Customer satisfaction has a significant effect on repurchase intention.